Native Desorption Electrospray Ionization Liberates Soluble and Membrane Protein Complexes from Surfaces. Issue 46 (18th September 2017) - Ambrose, Stephen; Housden, Nicholas G.; Gupta, Kallol; Fan, Jieyuan; White, Paul; Yen, Hsin‐Yung; Marcoux, Julien; Kleanthous, Colin; Hopper, Jonathan T. S.; Robinson, Carol V.
Abstract: Mass spectrometry (MS) applications for intact protein complexes typically require electrospray (ES) ionization and have not been achieved via direct desorption from surfaces. Desorption ES ionization (DESI) MS has however transformed the study of tissue surfaces through release and characterisation of small molecules. Motivated by the desire to screen for ligand binding to intact protein complexes we report the development of a native DESI platform. By establishing conditions that preserve non‐covalent interactions we exploit the surface to capture a rapid turnover enzyme–substrate complex and to optimise detergents for membrane protein study. We demonstrate binding of lipids and drugs to membrane proteins deposited on surfaces and selectivity from a mix of related agonists for specific binding to a GPCR. Overall therefore we introduce this native DESI platform with the potential for high‐throughput ligand screening of some of the most challenging drug targets including GPCRs. Abstract : Folded soluble and membrane proteins can be released directly from surfaces using a desorption electrospray ionization source coupled to a high‐resolution mass spectrometer. Desorbed protein complexes maintain non‐covalent interactions enabling rapid measurement of subunit stoichiometries and capturing specific ligand binding to a GPCR.